Conscious sedation with midazolam intravenously for a patient with Parkinson's disease and unpredictable chorea-like dyskinesia. Issue 6 (July 2018) - Shibuya, M.; Hojo, T.; Hase, Y.; Fujisawa, T.
Abstract: Oral surgery can be difficult in patients with chorea-like dyskinesia, which is common in those on long-term levodopa medication for Parkinson's disease, and we know of no conclusive evidence to indicate whether conscious sedation with midazolam is effective in such cases. We report a patient in whom levodopa-induced chorea-like dyskinesia disappeared when midazolam was given intravenously for conscious sedation.